The Relationship between Emotional Intelligence and Students' Learning Discipline in Surau Extracurricularies at Baiturrahmah Middle School, Padang City - Rahmawati, Lili; Solfema, Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
The Relationship Between Emotional Intelligence and Learning Discipline of Students at Extracurricular Surau at Baiturrahmah Middle School, Padang City. Thesis. Faculty of Science Education. Padang State University. This research was motivated by the low level of student learning discipline in the extracurricular surau at Baiturrahmah Middle School, Padang City. This is presumably due to the relationship between emotional intelligence and students' learning discipline. This study aims to look at the description of emotional intelligence, the description of learning discipline, and to know the relationship between emotional intelligence and students' learning discipline. This study uses a quantitative method with a correlational type. The population in this study were students with a total population of 58 students and the sample in this study totaled 36 students. The sampling technique used proportionate stratified random sampling. Data collection techniques using questionnaires or questionnaires. And for data analysis techniques using the percentage formula and product moment correlation formula.The results showed that: (1) Emotional intelligence is categorized as low, (2) Learning discipline is categorized as low, (3) There is a significant relationship between emotional intelligence and student learning discipline in the extracurricular surau at Baiturrahmah Middle School, Padang City. It is recommended to: (1) Students are able to manage their emotions well, (2) Schools can work together with parents of students to help improve children's emotional intelligence, (3) It is hoped that future researchers can identify other factors or other variables.